2015
DOI: 10.1101/sqb.2015.80.027557
|View full text |Cite
|
Sign up to set email alerts
|

How Transcription Networks Evolve and Produce Biological Novelty

Abstract: The rewiring of gene regulatory networks over evolutionary timescales produces changes in the patterns of gene expression and is a major source of diversity among species. Yet the molecular mechanisms underlying evolutionary rewiring are only beginning to be understood. Here, we discuss recent analyses in ascomycete yeasts that have revealed several general principles of network rewiring. Specifically, we discuss how transcription networks can maintain a functional output despite changes in mechanism, how spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 70 publications
0
24
0
Order By: Relevance
“…While transcriptional networks can undergo rapid rewiring at the level of enhancer binding sites during yeast, insect and mammalian evolution [54,55], the direct transcriptional targets of Lef1 mediating hypothalamic neurogenesis are still unknown. We have identified Tcf/Lef consensus binding sites in zebrafish and mouse Crhbp and Pmch loci, but it remains important to determine whether these 2 genes are direct targets of Lef1, or are instead lost as a secondary result of neurogenesis defects in mutants.…”
Section: Discussionmentioning
confidence: 99%
“…While transcriptional networks can undergo rapid rewiring at the level of enhancer binding sites during yeast, insect and mammalian evolution [54,55], the direct transcriptional targets of Lef1 mediating hypothalamic neurogenesis are still unknown. We have identified Tcf/Lef consensus binding sites in zebrafish and mouse Crhbp and Pmch loci, but it remains important to determine whether these 2 genes are direct targets of Lef1, or are instead lost as a secondary result of neurogenesis defects in mutants.…”
Section: Discussionmentioning
confidence: 99%
“…Rewiring of gene regulatory networks is an important mechanism of evolutionary adaptation [75]. It has, for example, recently been shown that the zinc cluster protein Ppr1 regulates pyrimidine biosynthesis in budding yeast but allantoin catabolism in C .…”
Section: Orthologs Of Ecm22 Upc2 Sut1 and Sut2 In Other Speciesmentioning
confidence: 99%
“…Nocedal and Johnson [7] write “We do not yet understand how a large network, composed of many transcription regulators and hundreds or thousands of target genes, forms in the first place.” We believe that considering only cases in which one transcription factor is switched with another will be inadequate to describe the evolution of networks. They also write “A change even in the regulation of a single gene can have important consequences in modern species’....…”
Section: Resultsmentioning
confidence: 99%
“…A motif is a short segment in the DNA sequence, between 6–20 nucleotide pairs, usually fewer than 10, that can be positioned at different locations within the regulatory region of a gene [7]. Tanay et al [8] focus on identifying motifs that are “enriched”, i.e., the motif occurs in multiple species, controlling analogous regulons in those species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation